2020
DOI: 10.1155/2020/1410808
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding Regional Mobility Patterns Using Car-Hailing Order Data and Points of Interest Data

Abstract: Car hailing is undergoing rapid global development, thereby providing new opportunities and challenges to operators and transport engineers due to uneven or irregular demand in certain areas. To date, only a limited number of studies have analyzed regional mobility patterns or anomaly detection. This study therefore proposes a methodology for recognizing regional mobility patterns using car-hailing order datasets and point of interest datasets. More specifically, we detect regional mobility patterns by incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Journal of Advanced Transportation has retracted the article titled "Understanding Regional Mobility Patterns Using Car-Hailing Order Data and Points of Interest Data" [1]. Following publication of the article, the authors identified that the method was verified only by comparison of the model and statistical results.…”
mentioning
confidence: 99%
“…Journal of Advanced Transportation has retracted the article titled "Understanding Regional Mobility Patterns Using Car-Hailing Order Data and Points of Interest Data" [1]. Following publication of the article, the authors identified that the method was verified only by comparison of the model and statistical results.…”
mentioning
confidence: 99%